Cardiomyopathy. Issue 5 (May 2020) - Moncrieff, Gregor; Williams, Howell; Bond, Richard
The European Society of Cardiology (ESC) defines cardiomyopathies as structural or functional abnormalities of the ventricular myocardium not caused by coronary artery disease, valvular disease, hypertension or congenital heart disease. Presentation can range from asymptomatic patients with abnormal investigations or family history, to arrhythmia, thromboembolic disease, progressive heart failure or sudden cardiac death. Early diagnosis and referral to specialist services is important, as treatment can reduce both morbidity and mortality. Investigation and management are undertaken in secondary or tertiary care. GPs with a good working knowledge of cardiomyopathy will be alert to key features of the history, examination and electrocardiogram findings that facilitate prompt referral. Appreciation of the heritable nature of many cardiomyopathies is important in order to facilitate family screening for relatives of patients with cardiomyopathy.